Twin cities by trolley : the streetcar era in Minneapolis and St. Paul - Diers, John W.; Isaacs, Aaron, 1949- (University of Minnesota Press, 2007)
The recent development of light rail transit in the Twin Cities has been an undeniable success. Plans for additional lines progress, and our ways of shopping, dining, and commuting are changing dramatically. As we embrace riding the new Hiawatha light rail line, an older era comes to mindthe age when everyone rode the more than 500 miles of track that crisscrossed the Twin Cities. In Twin Cities by Trolley, John Diers and Aaron Isaacs offer a rolling snapshot of Minneapolis and St. Paul from the 1880s to the 1950s, when the streetcar system shaped the growth and character of the entire metrop.